2017
DOI: 10.1371/journal.pone.0189606
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induction by Mycobacterium indicus pranii promotes Mycobacterium tuberculosis clearance from RAW 264.7 macrophages

Abstract: Mycobacterium indicus pranii (MIP) is a potent vaccine candidate against tuberculosis (TB) as it has demonstrated significant protection in animal models of tuberculosis as well as in clinical trials. Higher protective efficacy of MIP against TB as compared to BCG provoked the efforts to gain insight into the molecular mechanisms underlying MIP mediated protection against Mycobacterium tuberculosis (M.tb). Autophagy, initially described as a cell survival mechanism during starvation, also plays a key role in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…assays to demonstrate autophagic activity in BCG and M.tb infected macrophages, 60,61 plays an indispensable role in autophagosome formation and processing of LC3, whereas knockdown of the protein results in impaired autophagy in gynecologic tumors. 37 These processes together with other up-regulated proautophagic regulatory genes AMBRA1, CTSS, FBXL20, and RAB24, participate in the autophagy flux by contributing to autophagy vesicle elongation, killing of pathogenic microorganisms, protein degradation, and cargo transport, respectively.…”
Section: Autophagy-related Genes Were Regulated By Fsf In Mh-s Cells mentioning
confidence: 99%
“…assays to demonstrate autophagic activity in BCG and M.tb infected macrophages, 60,61 plays an indispensable role in autophagosome formation and processing of LC3, whereas knockdown of the protein results in impaired autophagy in gynecologic tumors. 37 These processes together with other up-regulated proautophagic regulatory genes AMBRA1, CTSS, FBXL20, and RAB24, participate in the autophagy flux by contributing to autophagy vesicle elongation, killing of pathogenic microorganisms, protein degradation, and cargo transport, respectively.…”
Section: Autophagy-related Genes Were Regulated By Fsf In Mh-s Cells mentioning
confidence: 99%
“…indicus pranii as a booster to BCG via the aerosol route showed protective effect in a mice model of TB, inducing proinflammatory cytokines like IFN-γ, IL-12 and IL-17, and increased frequency of multifunctional T-cells [275]. In vitro studies showed that M. indicus pranii modulates pro-inflammatory responses via the TLR-4 pathway, activate the innate immunity [276] and induced autophagy in TB infected macrophages [277]. Clinical trials as adjunct therapy showed that it is safe with no significant side effects and able to clear the pathogens in TB relapse patients [278].…”
Section: (A) Pathogen-related Prophylactic Measures: Blocking the Tramentioning
confidence: 99%
“…Oleic acid, Catalase, Lowenstein-Jensen (LJ) Media were obtained from HiMedia Laboratories, India. GFP expressing M.tb was prepared by the method described in [11].…”
Section: Mycobacterial Culturementioning
confidence: 99%
“…The protocol used in our previous publication was followed [11]. Briefly, macrophages were seeded on coverslips were infected with GFP expressing M.tb for 4 h with subsequent stimulation with MIP-LAM / M.tb-LAM for 4 h. This was followed by Lysotracker-Red staining.…”
Section: Co-localization Of Mtb With Lysosomes In Lam Stimulated Macmentioning
confidence: 99%
See 1 more Smart Citation